Fasting and cancer: molecular mechanisms and clinical application. Issue 11 (November 2018) - Nencioni, Alessio; Caffa, Irene; Cortellino, Salvatore; Longo, Valter
Abstract The vulnerability of cancer cells to nutrient deprivation and their dependency on specific metabolites are emerging hallmarks of cancer. Fasting or fasting-mimicking diets (FMDs) lead to wide alterations in growth factors and in metabolite levels, generating environments that can reduce the capability of cancer cells to adapt and survive and thus improving the effects of cancer therapies. In addition, fasting or FMDs increase resistance to chemotherapy in normal but not cancer cells and promote regeneration in normal tissues, which could help prevent detrimental and potentially life-threatening side effects of treatments. While fasting is hardly tolerated by patients, both animal and clinical studies show that cycles of low-calorie FMDs are feasible and overall safe. Several clinical trials evaluating the effect of fasting or FMDs on treatment-emergent adverse events and on efficacy outcomes are ongoing. We propose that the combination of FMDs with chemotherapy, immunotherapy or other treatments represents a potentially promising strategy to increase treatment efficacy, prevent resistance acquisition and reduce side effects. This Opinion discusses the potential of fasting and fasting-mimicking diets to help overcome toxicities induced by anticancer therapy. The differential response of normal and cancer cells undergoing starvation is argued to make normal cells less sensitive to therapy-induced toxicity, while cancer cells become more sensitive to therapy-induced cell death.